COVID-19 and Co-production in Health and Social Care Research, Policy and Practice Volume 2: Co-production Methods and Working Together at a Distance - Williams, Oli; Tembo, Doreen; Ocloo, Josephine; Kaur, Meerat; Hickey, Gary; Farr, Michelle; Beresford, Peter (Policy Press, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Groups most severely affected by COVID-19 have tended to be those marginalised before the pandemic and are now being largely ignored in developing responses to it. This two-volume set of Rapid Responses explores the urgent need to put co-production and participatory approaches at the heart of responses to the pandemic and demonstrates how policymakers, health and social care practitioners, patients, service users, carers and public contributors can make this happen. The second volume focuses on methods and means of co-producing during a pandemic. It explores a variety of case studies from across the global North and South and addresses the practical considerations of co-producing knowledge both now - at a distance - and in the future when the pandemic is over."